Hak Ijbar Wali Nikah dalam Kajian Historis Fiqh Shâfi’î - Syaiful Hidayat (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2015)
Is currently still found practice of coercion marriages by the guardian (especially father) to his daughter. The imposition of this marriage is more commonly referred to as hak ijbar. Anvil used is an understanding of hak ijbar the inherent certainty for a guardian over her daughter. Are Syafi’i schools seen as dominant calling for hak ijbar based on the behavior Apostle who married ‘Aisyah at age so young and in the absence of discussions between Abu Bakr and ‘Aisyah be a sign of existence hak ijbar. However, as the Indonesian people, beside fiqh also must submit and obedient the laws and all regulations thereunder, including the Islamic Law Compilation (KHI). In Article 72 KHI described; The revocation of a marriage is a marriage without a guardian or trustee executed by unauthorized and marriage carried out by force. This means the hak ijbar not allowed because it constitutes coercion. This issue is interesting to examine the social side, especially the social history of women at the time of priest Syafi’i life. It aims to determine the general condition and position of women in the social institution that has its historical position which will then be used as a prediction projective.